Computer-mediated communication as an effective communication tool in school organizations, fraternities and sororities in UP Baguio - Agnes, Katrina D. (2003)
The study focused on finding out whether or not CMC users in UP Baguio perceive Computer-Mediated Communication or CMC as an effective communication tool in organizations, fraternities and sororities. It also determined the different reasons why members of organizations, fraternities and sororities use CMC and the satisfaction they get from the use. Analysis of data was done by means of one-shot survey through the use of questionnaires floated inside the university campus. Results reveal that there are three reasons for CMC use and these are Information, Interaction and Communication. Among the three , information was cited as the most popular reason for CMC use. Results also reveal that the electronic groupware system is the most frequented CMC system by members of organizations, fraternities and sororities UP Baguio. Moreover, CMC users perceive CMC as advantageous than other mediated communication. In conclusion, respondents of this study perceive CMC as an effective communication tool i their organization, fraternities and sororities and that majority of them is satisfied with how CMC works in their respective groups -- Author's abstract.
Thesis (Bachelor of Arts) -- University of the Philippines Baguio, 2003.
Includes bibliographical references.
Keywords: Telematics -- Social aspects; Computer networks -- Social aspects; Interpersonal communication